Comparison of bone mineral density in soccer players and professional referees - López García, R.; Lagunes Carrasco, JO.; Carranza García, LE.; Navarro Orocio, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The aim of this study was to compare bone mineral density (BMD) of soccer players and professional referees. There were made bone mineral density measurements with the dual x-ray absorptiometry equipment (DEXA) to 27 players (19.81 ± 1.14 years old) and 22 referees (24.95 ± 3.54 years old) from the second division of the Mexican professional soccer league (Liga MX) where the areas of the spine, hip, ribs, arms, legs and full body were evaluated. It was used the statistical program SPSS (21.0), using the test for independent samples of the t of Student, considering the significance value of p ≤ .05. The players achieved a higher BMD than the referees in most regions of the body, finding only significant difference in the legs and hip (p ≤ .05). The high mineralization of the legs of the players is due to the high contact repeatedly to the game ball, although a higher BMD was also obtained in the referees than in other sports of other studies. Thus concluding that the practice of refereeing in football is positive for bone strengthening. However, more studies on BMD in referees, officials and judges in football and in other disciplines are needed.